Development of a simple algorithm to detect different types of freestyle jumps and jumps during skiing - Kranzinger, C.; Martinez, A.; Kranzinger, S.; Stöggl, T. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Jump detection via inertial measurement units (IMUs) to monitor athletes is of high interest in many sports (e.g. volleyball 1,2, figure skating 3, snowboarding 4, ski jumping 5). This work aims to develop an algorithm that detects jumps under different skiing conditions: freestyle jumps (big air, jumping hills) and jumps during normal skiing based on IMU data. The IMUs are attached to the skiers` boots, which allows stable and consistent data recording 6.